Why Music in Neurology? - Raglio, Alfredo; Granieri, Enrico (Journal of Neurological Research And Therapy, 2015)
In the last years we could find many uses of music in different clinical settings, also in the field of neurology. In this field empirical results, but also scientific studies, showed the efficacy of music interventions on psychological, cognitive and motor aspects. This is consistent with strong effects of music on brain areas. Music can stimulate and modulate/regulate cognitive functions, behaviors, movements and emotions. Music plays an important role also from a psychological point of view, increasing motivation and promoting relationships and communication. Literature has showed how music interventions can improve behavioral, cognitive, motor, psychological, relational and emotional outcomes in different neurological pathologies. Significant results are present in particular in dementia, stroke and Parkinson's disease. We can find also minor results and qualitative research approaches in multiple sclerosis and in other brain injury such as vegetative and minimally conscious state. More rigorous methodologies and criteria of research are needed to support and strengthen the therapeutic value of music.
Keywords: Music; Music Therapy; Evidence-Based Music Therapy; Neurological Diseases